Exit theater - Lala, Mike, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2016)
Selected by Tyrone Williams for the 2016 Colorado Prize for Poetry, Exit Theater casts classical elegy, with dazzling formal innovation, into a staggering work of contemporary, political polyphony. Through monologues, performance scripts, and poems of exquisite prosody, Mike Lala examines the human figure--as subject and object, enemy and ally--in the context of a progressively de-figured and hostile world. Catullus, Shakespeare, Cy Twombly, and Lydia Delectorskaya echo across engagements with Israeli generals, accused terrorists, State Department employees, nuclear scientists, Saturday Night Live actors, war criminals, malware, and a host of mythic, literary, and half-extant spectral characters. Amid the cacophony, Lala implicates every actor, including himself, in a web of shared culpability vis-a-vis consumerism, representation, speaking, writing, and making art against the backdrop of the endless, open wars of a post-Cold War, post-2001 era. Exit Theater is a debut of and against its time--a book about war, art, and what it means to make art in a time of war.
Say Goodbye to the Shores -- Say to the Shores. Suite w/ a View for the Ends of Our Days -- Lydia -- The Fire that Consumes All before It -- Portraits of the Artists as Their Own Subjects -- In the Gun Cabinet. drapery -- there's a violence -- as it emptied -- nocturne -- a closet -- on the mantle -- & here from my window -- the bodies you inhabit -- a thief -- the theater of fear -- two playgrounds -- in the hospitality of war -- Interview -- Exit Theater. Song / Little Myth -- See: Enemy -- As Her Myriad Aggressors -- As His Myriad Objections -- Twenty-Four Exits -- If Nothing Else, Pleasure -- Self_Interrogation.
Keywords: Consumption (Economics) -- Moral and ethical aspects -- Poetry; Justice -- Poetry